PERBANDINGAN MORFOLOGI INFLEKSI BAHASA INDONESIA DAN BAHASA INGGRIS - I Gede Dwi Setiadi; I Wayan Putra Adi Subawa (Universitas Warmadewa, 2025)
This article examines the comparative morphology of inflection in Indonesian and English, aiming to identify structural and functional differences in the grammatical formation of verbs and nouns. The study employs a documentary method by collecting data from Indonesian and English corpora and applying descriptive-comparative analysis based on structural morphology and language typology theories. The findings indicate that English features a productive and complex inflectional system, with obligatory word form changes reflecting tense, person, and number. In contrast, Indonesian is analytic and lacks formal inflection, relying instead on contextual markers, auxiliary words, and other morphological processes such as reduplication to convey equivalent meanings. The discussion reveals that these differences reflect the fundamental typological nature of each language and affect sentence structure, meaning strategies, and practical implications in language learning and translation. The conclusion emphasizes the importance of understanding cross-morphological structures in linguistic studies and intercultural language applications.